Radiomic Study for Objectification of Diagnostics and Complex Treatment of Glioblastoma - Ya. O. Nikulshina; A. N. Redkin; A. V. Kolpakov; M. A. Zakharov (Креативная хирургия и онкология, 2022)
Introduction. Glioblastoma is a neuroepithelial malignant brain tumour of predominantly astrocytic origin with an aggressive course and an extremely unfavorable prognosis. Since the median of overall survival with glioblastoma is 14.6 months after complex treatment that includes a combination of surgical treatment, radiation therapy and chemotherapy, the development a personalized approach in the diagnosis and treatment of glioblastomas is appeared to be urgent.Materials and methods. MRIs of a patient undergoing chemoradiotherapy for glioblastoma G4 were performed on the following MRI scanners: Philips Ingenia 1.5T and Philips Ingenia Ambient 1.5T. The analysis of MR-images was carried out using the Matlab 2021 apps.Results and discussion. MR-images were analyzed before and after surgery, and after a course of chemoradiotherapy. The statistical characteristics of the local brightness distribution of the lesion image, which are described by statistical texture parameters, were analyzed as informative features of the lesion area on the images. Initial confirmation of the ability to objectify diagnosis and treatment using the above statistical parameters of T2 MR images of lesion area has been obtained.Conclusion. The aim of further research in this area is to use radiomic study for planning and monitoring the treatment of high-grade gliomas, estimate disease outcomes, and analyze the response to complex treatments in a predictive way.